2020
DOI: 10.1016/j.ajog.2019.11.1285
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse surgery and quality of life—a nationwide cohort study

Abstract: BACKGROUND: Patient satisfaction and health-related quality of life are nowadays considered as the most important outcomes of pelvic organ prolapse treatment, and large, prospective clinical studies reporting the patient-reported surgical outcomes are needed. OBJECTIVE: To evaluate the effect of female pelvic organ prolapse surgery on health-related quality of life and patient satisfaction and to determine predictors of outcome. STUDY DESIGN: This prospective nationwide cohort study consisted of 3515 women und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 29 publications
2
45
0
2
Order By: Relevance
“…Pelvic organ prolapse surgery has been shown to improve in both generic and disease‐specific patient‐reported outcome measures, 2,8,9 but the findings of this study demonstrate that the quantified health gains are dependent on the chosen patient‐reported outcome measure. In our study, the three patient‐reported measures (PFDI‐20, 15D, and PGI‐I) were only weakly correlated, and the proportion of concordant ratings between instruments varied between 31.1% and 72.8%.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Pelvic organ prolapse surgery has been shown to improve in both generic and disease‐specific patient‐reported outcome measures, 2,8,9 but the findings of this study demonstrate that the quantified health gains are dependent on the chosen patient‐reported outcome measure. In our study, the three patient‐reported measures (PFDI‐20, 15D, and PGI‐I) were only weakly correlated, and the proportion of concordant ratings between instruments varied between 31.1% and 72.8%.…”
Section: Discussionmentioning
confidence: 70%
“…However, it is unknown how consistently different validated questionnaires evaluate the changes in HrQoL after POP surgery. We 8 and others 2,9 have previously shown that POP surgery leads to improvement in both generic and disease‐specific PROM measures, but it is unknown how strongly these measures are correlated, that is, whether those among whom improvement in generic HRQoL is detected are the same women who report symptom alleviation. Furthermore, as many generic instruments such as 15‐dimensional instrument (15D) measure also sexual function and excretion symptoms, it is important to assess whether they capture the symptom alleviation detected by symptom‐specific instruments such as Pelvic Floor Distress Inventory‐20 (PFDI‐20) and its subscales.…”
Section: Introductionmentioning
confidence: 99%
“…However, access to POP surgery in low income countries is very limited because it is expensive and the skilled personnel to perform the surgery are few [ 25 ]. Surgery for symptomatic POP has been shown to improve the QOL in high income countries [ 5 , 13 , 26 28 ]. However, in low income countries including Uganda, the impact of surgery on QOL is rarely reported yet this evidence is important for advocacy in scaling up treatment for POP in these resource limited settings where women with POP face various challenges in accessing care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…POP can have significant effects on a woman's quality of life, along with their physical and mental health (1). The global incidence of POP is approximately 20% and is increasing on an annual Original Article basis (2,3). Multiple factors including age, menopause, parity, obesity (4), hysterectomy, and connective tissue disorders have been reported to be in association with POP development (5,6).…”
Section: Introductionmentioning
confidence: 99%